Syntheses and methylations of 2,3-dioxopyrrolidines with different amines / Anis Raehana Bt Abd Rasid - Abd Rasid, Anis Raehana (Faculty of Applied Sciences, 2009)
In this research, sodium diethyl oxalate that has been used as the starting material was reflux together with amine and 4-methoxy benzaldehyde for 30 minutes via one-pot reaction. Two different amines which is benzyl amine and methyl amine were used for the variation of the result. Then, the products forms via one-pot reaction were being alkylated by using methyl iodide as the alkylating agent. The 2,3- dioxopyrrolidine derivatives in ethanol was refluxed with the methyl iodide and potassium carbonate. The expected alkylation was preferred at C4 position on the pyrrolidine ring because the α-hydrogen is more acidic since it is surrounded by the carbonyl carbon and benzene group. But the result obtained through the characterization of 1H NMR spectrum show that there is O-alkylation instead of Calkylation. The methyl group is attached to the oxygen at C3 position on the pyrrolidine ring system. Chromatography analysis also has been proposed to identify the present of other impurities. On the TLC, several spots were observed represent the major product, some unreacted starting material and impurities product. The desired product has been separated from the others material and product through the column chromatography.